Breastfeeding practices and associated factors at the individual, family, health facility and environmental levels in China. (30th June 2020) - Li, Jia; Nguyen, Tuan T.; Wang, Xiaobei; Mathisen, Roger; Fang, Jin
Abstract: We examined the association between breastfeeding practices and associated factors using cross‐sectional data from face‐to‐face interviews with 9, 745 mother–child dyads in China. The study collected information on breastfeeding practices and potential associated factors at the individual, family, health facility and environmental levels in China. We used survey commands in Stata to consider sampling weight and survey design effects. Although breastfeeding was the norm (97.4% ever breastfed), the prevalence of early initiation of breastfeeding (EIBF) in 0–11 months old was 8.2%, exclusive breastfeeding (EBF) in 0–5 months old was 27.8% and breastfeeding on the previous day in 6–11 months old was 77.5%. The prevalence of EIBF was lower for caesarean delivery and among mothers belonging to ethnic minority groups. The prevalence of EBF was higher among mothers who practiced EIBF, received information that encouraged breastfeeding and knew that a baby should be breastfed on demand and exclusively. By contrast, the prevalence of EBF was lower in mothers who received infant formula advice or felt uneasy breastfeeding in public places. The prevalence of breastfeeding on the previous day was higher among mothers whose partners supported breastfeeding and who knew about timing of colostrum production, EBF for 6 months, and to nurse more to stimulate milk production. The prevalence of breastfeeding on the previous day was lower in mothers who received infant formula advice or felt uneasy breastfeeding in public places. In conclusion, we found that the prevalence of EIBF and EBF practices in China was low and associated with factors at individual, family, health facility and environmental levels.